The Experience of Adult Clients with Type 2 Diabetes Mellitus at the Cigugur Tengah Public Health Center - ., Budiman; ., Nadirawati; Ariansyah, Alfi (KnE Life Sciences, 2021)
Type 2 diabetes mellitus is a health problem that tends to increase every year and has the most complications among other generative diseases. This study aimed at gaining a deeper understanding of the meaning of type 2 diabetes mellitus treatment for adult clients. The study used a qualitative approach with a phenomenological design. Data were collected through in-depth interviews, and field notes were analysed by applying the Collaizi technique. In total, five individuals were included in the study. The study included seven themes: risk factors for type 2 diabetes; changes experienced by the patients of type 2 diabetes; efforts made by the patients to overcome diabetes; behaviour towards diet and treatment, support from the family; expectations of the patients; and complications faced by the patient. For this reason, the authorities, especially nurses at the Cigugur Tengah Public Health Center, should continue to monitor and counsel DM patients so that the complications due to DM can be resolved as early as possible. Keywords: experience, adult, type 2 DM